Estimasi Ketersediaan Ikan dan Kebutuhan Bahan Baku Industri Pengolahan Ikan Di PPN Brondong Lamongan - Lisa Nur Hidayah; Iin Solihin; Eko Sri Wiyono; Mochammad Riyanto (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2022)
The Brondong Fishing Port is the largest in East Java. The catches landed in the Brondong fishing port increase, but they are insufficient to meet the raw material necessity of the existing processing industry. The study aims at estimating fish availability and the necessity of raw materials for the fish processing industry in the Brondong fishing port. This research was conducted from January to March 2022 by using a descriptive method. Data were collected through interviews and a literature study. The results revealed that the installed capacity for eight fish processing industries in the Brondong fishing port counted as 123,300 tons/year. Starry triggerfish, Lizard fishes, Streaked spine foot, freckled goatfish, squid, croaker, red snapper, spotted sil, grouper, threadfin breams, hardtail, big eyes, and yellow pike conger were all necessary for the processing industry. In contrast, the estimation of fish availability for the fish processing industry at Brondong fishing port counted as 45,086 tons/year. It indicated a gap between fish availability and the demand from the fish processing industry in the Brondong fishing port. This may impact the fish processing industry's development in the Brondong fishing port. Keywords: Raw material necessity, fish availability, fish processing industry